HOLY DEFENSE OF THE COUNTRY - Yusupov Arabboy Bahodirjon Ogli; Abduganiyev Jamhurbek Isroil Ogli; Ubaydullayev Saidakbar Saydalievich Ogli (Galaxy International Interdisciplinary Research Journal, 2021)
This article is about the love for the defense of the Motherland.